2003
DOI: 10.1108/13683040310509278
|View full text |Cite
|
Sign up to set email alerts
|

Simulation as an enabler for organizational excellence

Abstract: A case-based research approach is used to illustrate the power of modeling manufacturing performance measures and to help develop insights into the nature and problems evident when attempting to use simulation across different enterprise sectors. The research methodology used considered three speci®c companies, each with distinctive characteristics and attributes; a small to medium enterprise (SME), a medium to large enterprise (MLE) and a large enterprise (LE). From a cross-case analysis of the use of discret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Potentially, companies ranging from small to large can benefit significantly through the appropriate utilisation of DES. However, while there is a vast and evolving literature on applied DES studies, the majority of studies conducted tend to be within a larger firm context (Aqlan et al, 2014;Azadeh et al, 2011;Bengtsson et al, 2009;Byrne et al, 2010;Fowler and Rose, 2004;Liston et al, 2007;Mayer and Spieckermann, 2010;Nidumolu et al, 1998;O'Kane et al, 2007;Sharda and Bury, 2012 Aids in superior manufacturing facility design with less-costly mistakes Sources: Ahmed and Latif (2010), Banks (1999), Fowler and Rose (2004), Liotta (2012) and O'Kane (2003) Table I. Selection of potential benefits of DES to companies 164 JSBED 23,1 themselves to effectively adopting DES, such as the necessary level of organisational complexity, the required level and format of data needed for DES and the necessary budget to support DES.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potentially, companies ranging from small to large can benefit significantly through the appropriate utilisation of DES. However, while there is a vast and evolving literature on applied DES studies, the majority of studies conducted tend to be within a larger firm context (Aqlan et al, 2014;Azadeh et al, 2011;Bengtsson et al, 2009;Byrne et al, 2010;Fowler and Rose, 2004;Liston et al, 2007;Mayer and Spieckermann, 2010;Nidumolu et al, 1998;O'Kane et al, 2007;Sharda and Bury, 2012 Aids in superior manufacturing facility design with less-costly mistakes Sources: Ahmed and Latif (2010), Banks (1999), Fowler and Rose (2004), Liotta (2012) and O'Kane (2003) Table I. Selection of potential benefits of DES to companies 164 JSBED 23,1 themselves to effectively adopting DES, such as the necessary level of organisational complexity, the required level and format of data needed for DES and the necessary budget to support DES.…”
Section: Introductionmentioning
confidence: 99%
“…While the emphasis in research and implementation of DES studies in the past has mostly been focused on such large organisations, there are some reported cases where DES has been applied to SMEs (Ahmed and Latif, 2010;Byrne and Heavey, 2004;Geraghty and Heavey, 1999;Hvolby et al, 2012;Jain and Leong, 2005;Jarkko et al, 2013;Liotta, 2012;Mahfouz et al, 2011;Mosca et al, 2005;Nisula and Pekkola, 2012;O'Kane, 2003;Swarnkar and Harding, 2009). Studies of SME simulation have been sporadic and mostly explored on a one off, case-by-case basis (Hvolby et al, 2012;Jarkko et al, 2013;Mahfouz et al, 2011) which is in line with reported expectation, as investigating simulation within the SME context presents a number of additional challenges (Liotta, 2012;O'Kane, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer-based simulation can take many forms, but generally the technique is applied by developing a computer model using either a simulation language, package, tool or integrated environment system (O'Kane, 2003). Discrete-event simulation is "the modelling of a system as it evolves over time, by a representation in which the state variables change instantaneously at separate points in time" (Law and Kelton, 1991).…”
Section: Lean Park Homes Productionmentioning
confidence: 99%
“…Continuous assessment on the functionality and operability of the project product and feedback mechanism allow dynamic interaction and evaluation of the project's performance over the life cycle of projects (O'Kane, 2003).…”
Section: Framework For Simulation Analysismentioning
confidence: 99%